Investigation of Accuracy of a Calibrated Estimator of a Ratio by Modelling - Chadyšas, V.; Krapavickaitė, D. (Nonlinear Analysis: Modelling and Control, 2005)
Estimator of finite population parameter – ratio of totals of two variables – is investigated by modelling in the case of simple random sampling. Traditional estimator of the ratio is compared with the calibrated estimator of the ratio introduced by Plikusas [1]. The Taylor series expansion of the estimators are used for the expressions of approximate biases and approximate variances [2]. Some estimator of bias is introduced in this paper. Using data of artificial population the accuracy of two estimators of the ratio is compared by modelling. Dependence of the estimates of mean square error of the estimators of the ratio on the correlation coefficient of variables which are used in the numerator and denominator, is also shown in the modelling.
Keywords: finite population; ratio of two totals; simple random sampling; calibrated estimator